PENGARUH BAITUL MAAL WAT TAMWIL (BMT) TERHADAP PERKEMBANGAN USAHA DAN KESEJAHTERAAN ANGGOTA STUDI PADA BMT NGABAR - A'ang Yusril (Ngabari: Jurnal Studi Islam dan Sosial, 2023)
Baitul Maal wat Tamwil (BMT) is one of the financial institutions that protects the middle to lower classes from the interest system implemented by loan sharks who set high interest rates on their customers. One of the activities carried out by BMT institutions is coaching and financing or lending to members or customers to increase business capital that is run. Lack of financial access to microbusinesses is a problem that often occurs in microbusinesses. This study aims to analyze the effect of BMT financing and business coaching by the BMT on business development and improving the welfare of its members. This research was conducted at BMT Surya Kencana Ponorogo. The variables of this study include BMT financing, business development, business development, and welfare improvement. The sample in this study was 95 respondents.The analysis model in this study uses Partial Least Square (PLS). Statistical test results show that in the first hypothesis, BMT financing has a significant effect on business development, so that more and more funding is taken by customers or members, so that the business that is run will also develop. The results of the second hypothesis show that business development has a significant effect on business development, so that the higher the guidance provided, the business that is run will experience development. The results of the research on the third hypothesis show that BMT financing has a significant effect on improving welfare, so that more and more customer or member welfare financing has increased. The results of the fourth hypothesis show that business development has a significant effect on improving welfare, so that developing businesses will increase income and customers or members will experience increased welfare. Thus the financing and guidance that has been carried out by BMT has been in accordance with the principles of sharia and the main purpose of establishing a BMT financial institution.